Dielectric characteristics of novel composite nanomaterial. (2nd January 2020) - Petrov, Alexander; Zhaludkevich, Aliaksandr; Serdechnova, Maria; Hurski, Leanid; Kalanda, Nikolay; Karpinsky, Dmitry; Krivchenya, Dmitry; Fink, Dietmar
Abstract: Characteristic features of the PbZr0.54 Ti0.46 O3 formation in etched swift heavy ion tracks and investigations of dielectric properties of the obtained structures are reported in this work. PbZr0.54 Ti0.46 O3 compound is formed as a result of thermal treatment of film structures with identical composition being ion-beam sputtered on Si/SiO2 substrates. During the temperature dependence studies of the Si/SiO2 (PbZr0.54 Ti0.46 O3 ) structure at various frequencies their dispersion is obtained. It is shown that in the temperature range from 360 to 406°С the frequency dependence of the dielectric permittivity reaches maximum values which is explained by the presence of a ferroelectric phase transition.